Pemanfaatan Sampah Organik dan Tempurung Kelapa Menjadi Briket Ramah Lingkungan - Saragih, Guntar Marolop; Marhadi, Marhadi; Kalsum, Siti Umi; Nita, Rezi Yusdian (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the feasibility of producing environmentally friendly briquettes using organic waste and coconut shells as the main ingredients. 3 (three) briquette compositions, including: (1) 25% organic waste, equivalent to 75% coconut shell; (2) 75% organic waste, 25 percent coconut shell; and (3) 50% organic waste, 50 percent coconut shells. The research method used to analyze the water content, ash content and heating value of briquettes is a quantitative research method. The results of this research show that organic waste and coconut shells can be converted into environmentally friendly briquettes. Briquettes with a mixture composition of 75%:25% have a reduced ash percentage. Meanwhile, mixed briquettes containing 25%:75% have a low water content, meaning more coconut shell, the lower the water content and the better the properties of the briquettes.